Adela Speratti: the dream and the realization of the teaching profession in Paraguay (2022)
At the end of the 19th century, Latin America became the scene of significant changes; many of the countries of the continent underwent processes that had repercussions on politics, the economy, social relations and especially in the area we would like to deal with hereafter: education. In Europe, the optimistic ideas of positivism and scientism were triumphing on the back of the industrial revolution and technological advances, and the empire of the free market was flooding from Western Europe to all corners of the world, particularly the so-called former South American colonies that had not yet declared their independence half a century earlier.